Asiaticoside induces cell proliferation and collagen synthesis in human dermal fibroblasts - Linda Yuliati; Etik Mardliyati; Kusmarinah Bramono; Hans Joachim Freisleben (Universa Medicina, 2015)
Background Asiatiocoside, a saponin component isolated from Centella asiatica can improve wound healing by promoting the proliferation of human dermal fibroblasts (HDF) and synthesis of collagen. The skin-renewing cells and type I and III collagen synthesis decrease with aging, resulting in the reduction of skin elasticity and delayed wound healing. Usage of natural active compounds from plants in wound healing should be evaluated and compared to retinoic acid as an active agent that regulates wound healing. The aim of this study was to compare and evaluate the effect of asiaticoside and retinoic acid to induce greater cell proliferation and type I and III collagen synthesis in human dermal fibroblast.